Construct validity of the BarOn Emotional Quotient Inventory: youth version - Ugarriza, Nelly (2005)
The BarOn Emotional Inventory was standardized in a representative sample of 3.375 subjects (7-18 years old) from the urban area of Lima. The factorial structure was determined for the complete and brief version of the inventory by means of a principal component analysis with varimax rotation, including sex, age and type of school (state and private) variables. Four empirical factors were confirmed, including intrapersonal, interpersonal, adaptability and stress management as initially found by BarON (2000). Indicators of divergent validity between emotional intelligence and depression constructs were revealed.